Perancangan Sistem Informasi Pengarsipan Digital Data Pelanggan pada PT. Jambi Independent Press Berbasis Web - Miranda Miranda; Ronald Naibaho; Gunardi Gunardi (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
PT. Jambi Independent Press is one of the companies engaged in publishing newspapers in its data processing using Microsoft Excel, but there are still many obstacles in data processing, such as the difficulty of recording customer data archiving data, planning previously planned activities because the data search process is valued slow, data does not appear automatically so you have to input it repeatedly, and data cannot be integrated with each other because there is no database. The purpose of this study is to analyze the system that is currently running, in order to overcome the problems faced at PT. Jambi Independent Press, by designing a Customer Data Digital Archiving Information System Design at PT. Web-Based Jambi Independent Press. The research framework that will be carried out in solving the problems discussed is identifying, conducting information searches based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to problems faced by PT. Jambi Independent Press. The system development method uses the waterfall model, the implementation of this research uses the PHP Programming Language and MySQL DBMS, to produce data processing applications that are expected to facilitate data processing and report generation.